Polyglycerol-functionalized nanodiamond as a platform for gene delivery: Derivatization, characterization, and hybridization with DNA - Zhao, Li; Nakae, Yuki; Qin, Hongmei; Ito, Tadamasa; Kimura, Takahide; Kojima, Hideto; Chan, Lawrence; Komatsu, Naoki (Beilstein Journal of Organic Chemistry, 2014)
A gene vector consisting of nanodiamond, polyglycerol, and basic polypeptide (ND-PG-BPP) has been designed, synthesized, and characterized. The ND-PG-BPP was synthesized by PG functionalization of ND through ring-opening polymerization of glycidol on the ND surface, multistep organic transformations (–OH → –OTs (tosylate) → –N3) in the PG layer, and click conjugation of the basic polypeptides (Arg8, Lys8 or His8) terminated with propargyl glycine. The ND-PG-BPP exhibited good dispersibility in water (>1.0 mg/mL) and positive zeta potential ranging from +14.2 mV to +44.1 mV at neutral pH in Milli-Q water. It was confirmed by gel retardation assay that ND-PG-Arg8 and ND-PG-Lys8 with higher zeta potential hybridized with plasmid DNA (pDNA) through electrostatic attraction, making them promising as nonviral vectors for gene delivery.
Keywords: carbon-nanomaterials; click chemistry; DNA; gene delivery; nanodiamond; polyglycerol; polypeptides